Adjuvant treatment with Wu-Zi-Yan-Zong formula for abnormal sperm parameters associated with male infertility: a meta-analysis of randomized controlled trials - Cui, Feilun; Zhang, Yueshi; Fan, Yu (Frontiers in Pharmacology, 2025)
BackgroundWu-Zi-Yan-Zong (WZYZ) formula is a traditional Chinese botanical drug that has been used to treat male infertility. This meta-analysis aims to evaluate its effectiveness of the WZYZ formula as an adjuvant therapy for treating abnormal sperm parameters associated with male infertility.MethodsA comprehensive literature search was conducted using PubMed, Embase, Cochrane Library, Web of Science, SinoMed, Wanfang, and CNKI databases until December 12, 2024 to identify randomized controlled trials (RCTs) that assessed the effectiveness of the WZYZ formula as an adjuvant therapy for treating abnormal sperm parameters associated in men with infertility. For dichotomous data, the pooled results were summarized as risk ratio (RR) with 95% confidence intervals (CI), while continuous data were expressed as pooled weighted mean difference (WMD) with 95% CI.ResultsA total of 11 RCTs involving 951 men were identified. The pooled results showed that the WZYZ formula, when combined with control treatment, significantly improved the pregnancy rate of female partners (RR 1.68; 95% CI 1.34–2.11), semen volume (WMD 0.58 mL; 95% CI 0.28–0.89), sperm concentration (WMD 6.87 × 106/mL; 95%CI 4.24–9.51), total sperm motility (WMD 15.55%; 95% CI 10.38–20.72), forward grade (a) sperm motility (WMD 5.44%; 95% CI 1.86–9.01), forward grade (a + b) sperm motility (WMD 7.14%; 95% CI 4.04–10.23), abnormal sperm morphology (WMD −10.38%; 95% CI −15.72 to −5.03), and activity of the acrosome enzyme (WMD 8.02 × 106 μIU; 95% CI 3.58–12.46.ConclusionAdjuvant treatment with WZYZ formula significantly improves the pregnancy rate of female partners by improving several semen parameters in infertile men with abnormal sperm parameters. However, further well-designed RCTs with larger sample sizes are necessary to definitively determine the efficacy and safety of the WZYZ formula in treating abnormal sperm parameters associated with male infertility.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024629510.